If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(3z + -2) = 7 + -4z Reorder the terms: 10 + -1(-2 + 3z) = 7 + -4z 10 + (-2 * -1 + 3z * -1) = 7 + -4z 10 + (2 + -3z) = 7 + -4z Combine like terms: 10 + 2 = 12 12 + -3z = 7 + -4z Solving 12 + -3z = 7 + -4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4z' to each side of the equation. 12 + -3z + 4z = 7 + -4z + 4z Combine like terms: -3z + 4z = 1z 12 + 1z = 7 + -4z + 4z Combine like terms: -4z + 4z = 0 12 + 1z = 7 + 0 12 + 1z = 7 Add '-12' to each side of the equation. 12 + -12 + 1z = 7 + -12 Combine like terms: 12 + -12 = 0 0 + 1z = 7 + -12 1z = 7 + -12 Combine like terms: 7 + -12 = -5 1z = -5 Divide each side by '1'. z = -5 Simplifying z = -5
| 5t/6=30 | | 3x+5x-2x=33+3 | | 10÷8=25/x | | 12x+4y=24.56 | | -y-41=3 | | 17x-(7x-8)=28 | | 2j+22=50-10 | | K/4=24 | | -8y=-56 | | x^3+2xy^2-y^3=0 | | 3(4x-1)=24 | | 0.5(x+4)=3(x-1) | | G/8=25/12 | | 9x+8x-7x=17+3 | | 3(x-2)=2(c-6) | | x-2y+2z=-7 | | g+7=15 | | 4-x=3(x-1)-5 | | 35-19=x-19 | | 96=(x+4)x | | -x+9y=1 | | 7-g=12 | | y-8/9=9/10 | | 16x^2+24x-216=0 | | 4x+9x-7x=28+2 | | 24+g=49 | | v/8x=w/y | | y^2+10y+25-81=0 | | 16x^3y+4x^2y^2-42xy^3= | | 2(x-1)(x-6)=0 | | 3-3(z-3)=(3z-5)-7 | | 8a-(a-1)=3 |